Silent Tyrant: An Interpretation of Moses’ Silence in Josephus’ Antiquities 4.150–151 - Westwood, Ursula (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2024)
In the fourth book of the Jewish Antiquities, Josephus describes the rebellion of Zambrias against the authority of Moses. The rebel leader gives an impassioned speech critiquing the Mosaic law, to which the lawgiver gives no answer. Josephus’ willingness to compose speeches and to counter anti-Jewish calumnies makes this silence unexpected. To understand its possible implications, and with roles played by silence in classical literature as a background, this paper explores the meanings which unexpected silences can have throughout Josephus’ works, particularly focusing on the association with secrecy, popular silence, and the end of an argument. The investigation finds an unsettling association with tyrannical action, which suggests a possible awareness of the link between lawgivers and tyrants in archaic Greek politics.